Central Asia program - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Central Asian countries have enjoyed significant agricultural and economic growth and improvements in household welfare in the past decade. Nevertheless, its regional food systems remain highly vulnerable to global economic shocks, volatility in international food and commodity prices, weather shocks and long-term climate change. External economic and financial shocks have been particularly painful for Kyrgyzstan and Tajikistan, which rely heavily on food (cereal) imports and remittance incomes to maintain food security. Revenues from natural resources help mitigate the worst of these shocks in Kazakhstan, Turkmenistan, and Uzbekistan. Still, their ability to finance food imports at the national level does not always translate into better nutrition outcomes at the household level. Moreover, climate change can potentially trigger weather effects imperiling agriculture in all five of the countries.